Carbon-Based Nanomaterials for Delivery of Biologicals and Therapeutics: A Cutting-Edge Technology - Alok Mahor; Prem Prakash Singh; Peeyush Bharadwaj; Neeraj Sharma; Surabhi Yadav; Jessica M. Rosenholm; Kuldeep K. Bansal (C, 2021)
After hydrogen and oxygen, carbon is the third most abundant component present in the cosmos with excellent characteristic features of binding to itself and nearly all elements. Since ancient times, carbon-based materials such as graphite, charcoal, and carbon black have been utilized for writing and drawing materials. As these materials possess excellent chemical, mechanical, electrical, and thermal features, they have been readily engineered into carbon-based nanomaterials (CNMs) such as carbon nanotubes, graphene oxide, graphene quantum dots, nanodiamonds, fullerenes, carbon nano-onions, and so forth. These materials are now widely explored in biomedical applications. Thus, the emergence of CNMs has opened up a gateway for the detection, delivery, and treatment of a multitude of diseases. They are being actively researched for applications within tissue engineering, as vaccine vectors, and for the delivery of therapeutics to the immune system. This review focuses on the recent advances in various types of CNMs, their fabrication techniques, and their application in the delivery of therapeutics both in vitro and in vivo. The review also focuses on the toxicity concern of the CNMs and the possible remedies to tackle the toxicity issues. Concluding remarks emphasize all the CNMs discussed in the review over their possible biomedical applications, while the future perspectives section discusses the approaches to bring CNMs into the mainstream of clinical trials and their therapeutic applications.